Is there justification for 4 cycles of consolidation therapy in AML? - Schlenk, Richard Friedrich (Best practice & research, 2016)
The concept of postremission therapy in acute myeloid leukemia is quite old, dating back to a trial conducted in 1988 by the Cancer and Leukemia Group B. Yet even with more than 20 years of investigation into the optimal number of cycles for consolidation therapy, the answer is still not entirely clear. Dose intensity also has an impact on the number of courses of consolidation therapy administered, as do the cytogenetics of the patients. This review examines how to direct the future of consolidation therapy outside of allogeneic transplantation and discusses the issues to consider in choosing the number of courses of consolidation, including the effect minimal residual disease may have in guiding decisions regarding consolidation treatment.